Two novel heterozygous truncating variants in NR4A2 identified in patients with neurodevelopmental disorder and brief literature review - Song, Xiaozhen; Xu, Wuhen; Xiao, Man; Lu, Yanfen; Lan, Xiaoping; Tang, Xiaojun; Xu, Nanjie; Yu, Guangjun; Zhang, Hong; Wu, Shengnan (Frontiers in Neuroscience, 2022)
Pathogenic variants in the nuclear receptor superfamily 4 group A member 2 (NR4A2) cause an autosomal dominant neurodevelopmental disorder with or without seizures. Here, we described two patients presenting with developmental delay, language impairment, and attention-deficit hyperactivity disorder. Trio-based whole exome sequencing revealed two novel heterozygous variants, c.1541-2A > C and c.915C > A, in NR4A2. Both variants were identified as de novo and confirmed by Sanger sequencing. In vitro functional analyses were performed to assess their effects on expression of mRNA or protein. The canonical splicing variant c.1541-2A > C caused aberrant splicing, leading to the retention of intron 7 and a truncated protein due to an early termination codon within intron 7 with decreased protein expression, while the variant c.915C > A was shown to result in a shorter protein with increased expression level unexpectedly. The clinical and genetic characteristics of the previously published patients were briefly reviewed for highlighting the potential link between mutations and phenotypes. Our research further confirms that NR4A2 is a disease-causing gene of neurodevelopmental disorders and suggests alterations in different domains of NR4A2 cause various severity of symptoms.